Eastern boundary drainage of the North Atlantic subtropical gyre - Laiz, Irene; Pelegrí, Josep Lluís; Machín, Francisco; Sangrà, Pablo; Hernández Guerra, Alonso; Marrero-Díaz, Ángeles; Rodríguez-Santana, Ángel (Ocean Dynamics, 2012)
24 pages, 17 figures, 4 tables The eastern boundary of the North Atlantic subtropical gyre (NASG) is an upwelling favorable region characterized by a mean southward flow. The Canary Upwelling Current (CUC) feeds from the interior ocean and flows south along the continental slope off NW Africa, effectively providing the eastern boundary condition for the NASG. We follow a joint approach using slope and deep-ocean data together with process-oriented modeling to investigate the characteristics and seasonal variability of the interior-coastal ocean connection, focusing on how much NASG interior water drains along the continental slope. First, the compiled sets of data show that interior central waters flow permanently between Madeira and the Iberian Peninsula at a rate of 2.5±0.6 Sv (1 Sv = 106 m3 s-1 109 km s-1), with most of it reaching the slope and shelf regions north of the Canary Islands (1.5±0.7 Sv). Most of the water entering the African slope and shelf regions escapes south between the easternmost Canary Islands and the African coast: In 18 out of 22 monthly realizations, the flow was southward (-0.9±0.4 Sv) although an intense flow reversal occurred usually around November (1.7±0.9 Sv), probably as the result of a late fall intensification of the CUC north of the Canary Islands followed by instability and offshore flow diversion. Secondly, we explore how the eastern boundary drainage may be specified in a process-oriented one-layer quasigeostrophic numerical model. Non-zero normal flow and constant potential vorticity are alternative eastern boundary conditions, consistent with the idea of anticyclonic vorticity induced at the boundary by coastal jets. These boundary conditions cause interior water to exit the domain at the boundary, as if recirculating through the coastal ocean, and induce substantial modifications to the shape of the eastern NASG. The best model estimate for the annual mean eastward flow north of Madeira is 3.9 Sv and at the boundary is 3.3 Sv. The water exiting at the boundary splits ...